Protective Effect of Green Algae Ulva reticulata Against Pseudomonas aeruginosa in Drosophila Infection Model - Firzan Nainu; Rangga Meidianto Asri; M. Natsir Djide; Muhammad Ahsan; Rudi Arfiansyah; Sartini Sartini; Gemini Alam (HAYATI Journal of Biosciences, 2019)
The emergence of antibiotic-resistant Pseudomonas aeruginosa is one of main health issues in global communities. To overcome such threat, the discovery of novel antibacterial agents is indispensable. This study aimed to evaluate the in vivo antipseudomonal activity of Ulva reticulata extract in Drosophila model of infection. Ethanolic extract of Ulva reticulata was prepared using maceration method and the extract was subsequently assessed for its in vivo antibacterial effect against P. aeruginosa using survival assay, bacterial load enumeration, and gene expression analysis in the wildtype Drosophila. Survival and bacterial load analysis were further performed in a similar fashion on the mutant flies devoid of component responsible in the activation of immune responses against P. aeruginosa. Decline in the survival of infected host accompanied by augmentation of bacterial proliferation was documented in the wildtype Drosophila upon infection with P. aeruginosa. These phenotypic events were further amplified in immune-deficient mutant Drosophila. Nevertheless, improvement of host survivorship and reduction of bacterial burden were demonstrated in both wildtype or immune-deficient mutant flies upon treatment with Ulva reticulata extract after bacterial challenge. Our data demonstrated in vivo antipseudomonal activity of Ulva reticulata extract and thus provide a valuable information about its future potential for health promotion.